2002
DOI: 10.1152/jn.00665.2001
|View full text |Cite
|
Sign up to set email alerts
|

Block of Glutamate-Glutamine Cycle Between Astrocytes and Neurons Inhibits Epileptiform Activity in Hippocampus

Abstract: of glutamate-glutamine cycle between astrocytes and neurons inhibits epileptiform activity in hippocampus. 88: 2302-2310, 2002; 10.1152/jn.00665.2001. Recurrent epileptiform activity occurs spontaneously in cultured CNS neurons and in brain slices in which GABA inhibition has been blocked. We demonstrate here that pharmacological treatments resulting in either the block of glutamine production by astrocytes or the inhibition of glutamine uptake by neurons suppress or markedly decrease the frequency of spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 58 publications
9
86
0
Order By: Relevance
“…[25][26][27][28][29] In the central nervous system, neurons are metabolically coupled to astrocytes. Astrocytes are responsible to provide neurons with the glutamate-precursor glutamine and with lactate, which is used by neuronal cells as preferred energy substrates.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] In the central nervous system, neurons are metabolically coupled to astrocytes. Astrocytes are responsible to provide neurons with the glutamate-precursor glutamine and with lactate, which is used by neuronal cells as preferred energy substrates.…”
Section: Discussionmentioning
confidence: 99%
“…MSO has been widely used as a GS inhibitor in astroglia in studies of hyperammonemia, memory consolidation, and seizures, and its effects can be counteracted by glutamine application (Bacci et al, 2002;Suarez et al, 2002;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). One recent study has used MSO to examine the effect of inflammatory stimuli on activation of GS in astroglia and found that GS activation is related to glutamatergic receptor activation (Muscoli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This shuttle includes the uptake of excessive extrasynaptic glutamate and the production [via glutamine synthetase (GS)] and release from astroglia of glutamine, which is then taken up by neuronal elements to replenish the supply of glutamate (Zwingmann and Leibfritz, 2003;Hertz, 2004;Hertz and Zielke, 2004;Fonseca et al, 2005). A potent inhibitor of GS in astroglia is methionine sulfoximine (MSO), and its effects can be counteracted by glutamine application (Bacci et al, 2002;Blin et al, 2002;Suarez et al, 2002;Shin et al, 2003;Gibbs and Hertz, 2005;Tanigami et al, 2005;Liang et al, 2006). However, only one study has used MSO to investigate the involvement of astroglial GS in the effects of noxious stimuli on glutamatergic receptor-related events in astroglia (Muscoli et al, 2005), and no studies have tested its effects on central sensitization in functionally identified nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in vitro GS blockade has been reported to terminate pharmacologically induced seizures in rat brain slices (Bacci et al, 2002). Thus, GS blockade in vitro is anticonvulsive, and glutamine seems to be necessary for the maintenance of seizure activity.…”
Section: Introductionmentioning
confidence: 94%